Modifying the nonradiative decay dynamics through conical intersections via collective coupling to a cavity mode - Ulusoy, Inga; Gomez, Johana A.; Vendrell, Oriol (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2019)
The coupling of a molecular ensemble to the confined electromagnetic modes of a microcavity can strongly modify the photophysics and photochemistry of the molecules upon photoexcitation. We investigate here how collective coupling effects lead to modifications of the mechanisms and rates of photochemical processes, in particular, photodissociation and nonradiative decay in NaI and pyrazine, respectively. We show that, after direct excitation into the lower polaritonic states, the lower-energy light-matter hybrid states, the dynamics of the molecular ensemble coupled to light is very similar to the dynamics of the corresponding isolated molecules. Conversely, excitation into the upper polaritonic states results in more complex dynamics that involve as a first step the population transfer toward the manifold of intermediate dark states. These dynamics differ substantially from those of the isolated molecules and may result in measurable time delays for nonradiative decay or excited-state reaction mechanisms. Similarly, we describe how addition of a buffer of nonreactive molecules coupled to the cavity mode can be used to delay the onset of the photochemical processes of the reactive part of the ensemble, where the buffer medium is more effective in inhibiting the reactive process than only reactive molecules in the cavity.